The tacit design process in architectural design education - Dooren, Elise van; Dorst, Machiel van; Asselbergs, Thijs; Merrienboer, Jeroen van; Boshuizen, Els (Design and Technology Education: An International Journal, 2019)
The purpose of the architectural design studio is that students learn to think and act like designers. However, communication between teachers and students seems to be problematic. Teachers barely seem to explain how designers work, which may be confusing for students. To learn professional reasoning processes and strategies, different teaching activities are involved, such as modelling, coaching, scaffolding, reflection, exploration and articulation. In the design studio it seems tradition that teachers only ask questions, while not articulating the design process. This paper focuses on the research question of whether teachers in architectural design education articulate the main ‘designerly’ actions and skills, performed by expert designers, and if so, to what extent and in which manner? To answer these questions video-recordings of 13 tutorial sessions are analysed with the help of an educational framework of five generic elements. The framework consists of the basic design process actions and skills, and is specifically developed as a vocabulary for making the design process explicit and to train students in the design process elements. The main conclusion is that teachers refer to the design product in an implicit way. They leave it to the students to discover the structure and components of the design process more or less by themselves